The role of Al, Ba, and Cd dopant elements in tailoring the properties of c-axis oriented ZnO thin films - Ali, Dilawar; Butt, M. Z.; Arif, Bilal; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2017)
Highly c-axis oriented un-doped ZnO and Al-, Ba-, and Cd-doped ZnO thin films were successfully deposited on glass substrate employing sol-gel spin coating method. XRD analysis showed that all thin films possess hexagonal wurtzite structure with preferred orientation along c-axis. Field emission scanning electron microscope (FESEM) was used to study the morphology of thin films. The morphology consists of spherical and non-spherical shape grains. EDX analysis confirms the presence of O, Zn, Al, Ba, and Cd in the relevant thin films. The optical properties of thin films were studied using UV-Vis spectrometer. All thin films possess more than 85% optical transmittance in the visible region. Blue shift in optical band gap E-g has been observed on doping with Al, whereas doping with Ba and Cd resulted in red shift of E-g. Urbach energy E-u of all doped ZnO thin films was found to have excellent correlation with their band gap energy E-g. Moreover, E-g increases while Eu decreases on the increase in crystallite size D. Optical parameters E-g and E-u as well as structural parameters lattice strain and stacking fault probability also show excellent correlation with the B-factor or the mean-square amplitude of atomic vibrations < u2 > of the dopant elements. Electrical conductivity measurement of the thin films was carried out using two-point probe method. The electrical conductivity was found to increase with the increase in crystallite orientation along c-axis.
Keywords: ZnO; Sol-gel; XRD; Crystallite size; c-axis; Band gap energy; Debye-Waller factor